The industrial heritage in Itabira: history, memories and future perspectives - Souza, Gabriela Procópio de (2021)
The city of Itabira, located in the southeastern region of Brazil, has one of the largest and most important mining areas in the country, dating from the mid-20th century and which remain active today, exerting a great impact in the region and in the country. In addition to economic development, the mining industry brought major changes to the territory and significantly affected the landscape, the city and the lives of the inhabitants, leaving a strong industrial legacy that includes mines, ore processing plants, tailings dams and other industrial structures, that make the city a great symbol of the mining history in Brazil and an exceptional testimony to the social and economic changes caused by the extractive industry. Currently, the city faces serious environmental and social issues caused by mineral exploration and, towards the possibility of depleting mining resources, this study proposes, through strategies, proposals and guidelines, the valorization of its industrial heritage as an economic alternative for the future, thus reducing the impact of the end of iron ore exploration, overcoming the dependence of the mining sector and allowing to maintain and promote its industrial culture; RÉSUMÉ: La ville d'Itabira, située dans la région sud-est du Brésil, possède l'une des zones minières les plus grandes et les plus importantes du pays, datant du milieu du XXe siècle et qui reste active aujourd'hui, exerçant un grand impact dans la région et dans le pays. Outre le développement économique, l'industrie minière a apporté des changements majeurs au territoire et a considérablement affecté le paysage, la ville et la vie des habitants, laissant un héritage industriel fort qui comprend des mines, des usines de traitement du minerai, des digues de résidus et d'autres structures industrielles, qui font de la ville un grand symbole de l'histoire minière au Brésil et un témoignage exceptionnel des changements sociaux et économiques provoqués par l'industrie extractive. Actuellement, la ville est confrontée à de graves problèmes environnementaux et sociaux causés par l'exploration minière et, face à la possibilité d'épuiser les ressources minières, cette étude propose, à travers des stratégies, des propositions et des lignes directrices, la valorisation de son patrimoine industriel comme alternative économique pour l'avenir, ainsi réduire l'impact de la fin de l'exploration du minerai de fer, surmonter la dépendance du secteur minier et permettre de maintenir et de promouvoir sa culture industrielle.